CPD application process: lessons from organizers - Bandi, Shamsul Hadi; Hasan, Sharina Farihah (2006)
Continuous professional development (cpd) has been mooted as an efficient catalyst to provide the present and future quantity surveyors with up to date knowledge that will maintain their presence in the construction industry. in the case of quantity surveying profession in Malaysia, the framework of any cpd activities is governed by the board of quantity surveyors, Malaysia (bqsm). any organizers who wish to organize cpd programme should therefore, submit their application to the board. However, it was found out that the stages of the application process were not duly documented and conveyed to the potential organizers and therefore affect the planning, in term of overall timing of the event. ln view of this issue, this paper reports the outcome of a study on the stages that involve in CPD application process by BQSM. The paper highlights the key stages n the process and later suggests a maximum allowable time to process such an application. The methodology adopted for the study combine desk research and informal interviews conducted with BQSM CPD Secretariat. The finding is very significant to our current CPD scenario and it can help organizers to plan their CPD programme better and help Quantity Surveyors to cope with the faster pace of change in the construction industry.